2021
DOI: 10.1016/j.ultsonch.2021.105506
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultrasound in combination with other technologies in food processing: A review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(105 citation statements)
references
References 179 publications
(137 reference statements)
1
95
0
9
Order By: Relevance
“…Weak magnetic fields are better at activating microorganisms and promoting their growth [37] , [38] , [39] . Strong magnetic fields kill microorganisms [40] .…”
Section: Physical Fieldsmentioning
confidence: 99%
“…Weak magnetic fields are better at activating microorganisms and promoting their growth [37] , [38] , [39] . Strong magnetic fields kill microorganisms [40] .…”
Section: Physical Fieldsmentioning
confidence: 99%
“…Desta forma, o uso desta tecnologia enquadra-se, assim, no conceito de tecnologia verde, além de ser utilizada na geração de produtos de maior qualidade, segurança e estabilidade, e processos econômicos, com menor impacto ambiental. Neste contexto, o ultrassom apresenta potencial para aumento da produtividade e redução do tempo necessário para condução de operações de processamento (Singla & Sit, 2021).…”
Section: Aplicações Do Ultrassomunclassified
“…In various food-processing industries, ultrasound has been considered an efficient, green technology. In recent years, ultrasound has increasingly been used in combination with other technologies in the food industry [11] . It has been reported that high-intensity ultrasound can destroy the crystal structure of the okara fiber and enhance its water-holding capacity (WHC) [12] .…”
Section: Introductionmentioning
confidence: 99%